Frequency of movement in bed to assess risk of pressure ulcer - A systematized review / Häufigkeit von Bewegung im Bett zur Einschätzung der Dekubitusgefährdung - Eine systematisierte Übersichtsarbeit - Panfil Eva-Maria; Volmajer Zdenka; Taeymans Jan (Sciendo, 2014)
The key criteria for identification of pressure ulcer risk are mobility and activity. In practice and research, it is currently not possible to assess these criteria with reliable instruments. New technical methods allow a quantified metric measurement of the mobility of patients lying in bed. However, it is unclear how to interpret such data. Therefore, the aim of this systematized literature review was to identify (i) reference values for frequencies of movements during sleep, and (ii) critical values for the clinical diagnosis of pressure ulcer risk. A literature search was conducted in the MedLine, CINAHL, Trip Database, the Cochrane Library, PEDro, Google Scholar databases and by handsearching the reference lists of eligible manuscripts for the period 2008-2013. One review and nine primary studies were selected. Pressure ulcer risk studies showed poor methodological quality while they showed a high heterogeneity of the measurement methods for the detection of movement during sleep. This observed heterogeneity did not allow to compare the study results. Less studies reported reference values compared to studies reporting correlations with pathological conditions such as sleep quality and pressure ulcer risk. After critically reviewing the studies, no valid data on the frequency of movement during sleep and on critical values for the clinical diagnosis of pressure ulcer risk was found. To interpret the results of a new measurement method and its efficacy, more diagnostic studies and high-quality randomized controlled trials are needed.